Competency framework for specialist critical care nurses: A modified Delphi study. Issue 1 (2nd August 2019) - Zhang, Xiaoning; Meng, Kun; Chen, Shuang
Abstract: Background: The specialist critical care nurse plays a vital role in the delivery of evidence‐based practice, and specific competency guidance has been established to facilitate critical care nursing practice and education development in many developed countries. However, no research has been conducted to develop a competency framework for specialist critical care nurses in China. Aims and objectives: To construct a competency framework specific to specialist critical care nurses in China. Design and methods: A two‐phased procedure was implemented. In phase 1, a literature review and four focus groups were used to develop the initial competency framework, which consisted of 101 statements. During phase 2, three rounds of a modified Delphi process were conducted and involved a national panel of 30 experts, including physicians, specialist critical care nurses, managers, and educators, who responded to the survey using a 5‐point Likert‐type scale to indicate their level of agreement with the competency framework. A 75% threshold for each competency was used to achieve panel consensus. Results: Experts in the field of critical care responded to rounds 1 (n = 29), 2 (n = 28), and 3 (n = 28). Seventy‐eight competencies were agreed upon after round 1, increasing to 88 after round 2 and 92 after round 3. The final competency framework was classified into six domains: evidence‐based practice, complex decisions, professionalism, communication and co‐operation, education and development, and leadership. Conclusion: The output of this study is an expert consensus competency framework that provides a sound foundation for the assessment and training of specialist critical care nurses. Relevance to clinical practice: The proposed competency framework should be used to assess nursing performance, promote continuing professional development, and further improve the delivery of quality health care and optimal patient outcomes.